2016
DOI: 10.1016/j.nucmedbio.2016.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Detection of atherosclerotic plaques in ApoE-deficient mice using 99mTc-duramycin

Abstract: Apoptosis of macrophages and smooth muscle cells is linked to atherosclerotic plaque destabilization. The apoptotic cascade leads to exposure of negatively charged phosphatidylethanolamine (PE) on the outer leaflet of the cell membrane, thereby making apoptosis detectable using probes targeting PE. The objective of this study was to exploit capabilities of a PE-specific imaging probe, 99mTc-duramycin, in localizing atherosclerotic plaque and assessing plaque evolution in apolipoprotein-E knockout (ApoE-/-) mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 55 publications
0
15
0
Order By: Relevance
“…Specificity of 99m Tc-duramycin for detecting phosphatidylethanolamine in apoptotic cells was demonstrated by using a 99m Tc-labeled linearized duramycin molecule ( 99m Tc-linear duramycin) that lacks affinity for phosphatidylethanolamine. This control peptide is an inactive form of duramycin that does not bind to phosphatidylethanolamine and has a minimally altered structure and the molecular weight of duramycin, as previously described by others (29,30). 99m Tc-linear duramycin exhibited a rapid blood clearance, and the biodistribution was prominent in the kidneys and liver similarly to 99m Tc-duramycin.…”
Section: Discussionmentioning
confidence: 64%
“…Specificity of 99m Tc-duramycin for detecting phosphatidylethanolamine in apoptotic cells was demonstrated by using a 99m Tc-labeled linearized duramycin molecule ( 99m Tc-linear duramycin) that lacks affinity for phosphatidylethanolamine. This control peptide is an inactive form of duramycin that does not bind to phosphatidylethanolamine and has a minimally altered structure and the molecular weight of duramycin, as previously described by others (29,30). 99m Tc-linear duramycin exhibited a rapid blood clearance, and the biodistribution was prominent in the kidneys and liver similarly to 99m Tc-duramycin.…”
Section: Discussionmentioning
confidence: 64%
“…The exposure time for every imaging configuration in the optimization routine was set to one second. The activities are samples drawn from the measured bio-distribution data reported in [27] and are expressed in units of the percent injected dose per gram of the body weight of the mouse (% dose/g). The radius of the signal and its location are reported in units of millimeters.…”
Section: Resultsmentioning
confidence: 99%
“…It is an ideal target for detecting death including apoptosis and necrosis, which can specifically bind to PE with high affinity and low background [11] . Some studies had shown extensively application of 18 F or 99m Tc labelled duramycin for detecting apoptosis in ischemia reperfusion injury, atherosclerosis, and tumors [12][13][14][15][16] . In this study, we evaluated the feasibility that the 99m Tc-labeled duramycin used to monitor myocardial cell death in a mouse model of acute myocardial infarction.…”
Section: Introductionmentioning
confidence: 99%